Multiple functional meanings of prepositions Between ancient and late grammarians (Journal of the College of Basic Education, 2024)
In the study of prepositions, the subject of prepositions emerges as one of the most important topics that need research and contemplation, as it is one of the most important links in the Arabic sentence, and many meanings are associated with it that complete the meaning of the sentence through specification and clarification The aim of this is to explain the multiplicity of meanings of prepositions that many grammarians, ancient and modern, have proven in the texts of their books, and among those who restricted those meanings and gave each letter an original meaning to which what appeared to be contrary to it is attributed through interpretation, and among those who saw the multiplicity of meanings in the original and sought to investigate them. And analyze it. For all of this, the research title was chosen as (The multiplicity of functional meanings of prepositions between ancient and late The nature of this research required that it include a preface, followed by two chapters, then a conclusion, and it was supported by sources and references. As for the introduction, it discussed (the concept of pluralism and functional meaning), and the first section studied (the multiplicity of meanings of prepositions between those who prohibit and permit), and the second section examined (applications to the multiplicity of functional meanings of prepositions